OPTIMIZING ARABIC SPEAKING SKILLS BASED ON INTEGRATION OF LEARNING THEORY FRAMEWORK IN HIGHER EDUCATION - Sutaman Sutaman; Suci Ramadhanti Febriani (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2021)
This study aimed to investigate the implementation of the learning theory framework on learning Arabic speaking skills and explore the supporting factors of successful speaking skills instruction at the Ar-Raayah College of Arabic Language (STIBA) Sukabumi. This study used a descriptive qualitative approach with a case study research method. The data were collected by interviews and documentation. Data analysis included data collection, data classification, display data, and conclusion based on Milles and Huberman's theory. The results showed that the implementation of the learning theory in speaking skills instruction was found in a) learning speaking skills based on the theory of behaviorism by establishing a learning environment, memorizing vocabulary method, Arabic language competitions, and the application of conversations in daily activities; b) learning based on cognitive theory which is done by discussion and qawaid and tarjamah method, c) learning speaking skills based on the constructivism theory which implemented cooperative learning, contextual learning, language games, and song methods. The study also revealed that factors that support the successful learning of Arabic speaking skills are internal and external factors, such as self-motivation, language environment, teachers and native speakers, and adequate learning facilities.